A simplified plate theory for vibration analysis of composite laminated sector, annular and circular plate. (October 2019) - Zhang, Hong; Zhu, Rupeng; Shi, Dongyan; Wang, Qingshan
Abstract: A unified analysis model for vibration characteristics of composite laminated annular sector plate, circular sector plate, annular plate and circular plate with various elastic boundary conditions is established based on the simplified plate theory (SPT) and two-dimensional (2D) improved Fourier-Ritz method. It has significant advantages in the study of free and forced vibration of thin-to-moderately thick rotary composite laminated plates. Under the current framework, the displacement admissible functions of the rotary plate are generally expressed as superposition of simple periodic functions, which includes the multiplication of two cosine functions and two complementary polynomials. The introduction of these polynomials can effectively eliminate jumping or discontinuity at the boundaries. The vibration characteristics of the rotary plate can be obtained by Rayleigh-Ritz energy technique. The present method shows fast convergence and good accuracy. The parameterization study on geometric parameters, material parameters and boundary conditions has been carried out to systematically reveal the vibration characteristics of rotary composite laminated plates, which can be the benchmark for the future research. Highlights: A unified analytical model of laminated sector, annular and circular plate is established based on simplified plate theory. The vibration characteristics of composite laminated sector, annular and circular plate are studied. The effect of structural and material parameters are further discussed.